Keefektifan LKPD Berbasis Cerita "Pesut Mahakam" Untuk Meningkatkan Keterampilan Menyimak Kelas II Sekolah Dasar - Fitazkirah, Khanah; Istiq’faroh, Nurul; Putri, Nimas Fara Andriana (Jurnal Ilmu Sosial dan Budaya Indonesia, 2026)
Listening skills of second-grade elementary school students are still low due to passive and less contextual learning. This study aims to examine the effectiveness of the Student Worksheet (LKPD) based on the Dayak tribe story "Pesut Mahakam" in improving listening skills of second-grade students. The research employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The subjects were all 25 second-grade students of State Elementary School in Surabaya , selected using total sampling technique. Data were collected through listening tests (pretest and posttest), observation, and documentation. Data analysis used the N-Gain formula to measure the improvement of listening skills. The results showed that the average posttest scores increased compared to the pretest, with an N-Gain value of 0.4644, which falls into the medium category. The LKPD, equipped with folklore, attractive illustrations, and a barcode for animated video, proved to help students understand oral information better and increase their engagement and learning motivation. The study concludes that the LKPD based on the Dayak tribe story "Pesut Mahakam" is effective in improving listening skills of second-grade elementary school students. This product can serve as an alternative contextual teaching material that integrates local wisdom with audiovisual media.